A implantação de obras civis e de saneamento na Bacia do Una, em Belém do Pará, e as condicionantes relacionadas às características geológicas e geotécnicas - SILVA, Kleber Roberto Matos da (2004)
This Thesis presents the civil engineering works for implementation of drainage and sanitation facilities in the area of influence of the Una canal, in the city of Belém, in the State of Pará, Brazil, involving the installation of drainage, water and sewer nets as well as road construction. This project, known as Project Una, involves an area of 3.644 ha, corresponding to approximately 21% of the continental area of city, with great part of its surface below flood level, that is, up to 3,60 m above sea level. The stratigrafy of the project area is composed basically of a thick superficial layer of very soft organic clay, that in some cases may reach over 60 m deep, overling intercalation of medium to compact sand layers and medium to hard silty clay layers. Besides the construction difficulties in soils of this nature, this work presents the many problems to resolved, as the resettlement of families of risk areas, that is, families that are living on the bed of channels, hindering the draining of the served waters and pluvial waters; the compensations of shaky residences for the works; the lack of physical space for the setting up of the works; the instability of the slopes of the marginal road of channels; the difficulties of management in the of face the extensive encircle of the area; the relationships with the community, tumultuated in some moments and, mainly, the priority of some areas, in detriment of other, for the execution of the works, in the face of available resources. Based in technical reports, projects and the author's personal experiences the thesis makes a description of the project in its several aspects, as well, makes a critical review of it, under the civil engineering’s point of view, involving planning and executions aspects of the works, with the purpose of building and setting up of the knowledge, that promote the improvement in future development in the similar projects.